Hypofractionated versus conventional fractionated postmastectomy radiotherapy for patients with high-risk breast cancer: a randomised, non-inferiority, open-label, phase 3 trial. Issue 3 (March 2019) - Wang, Shu-Lian; Fang, Hui; Song, Yong-Wen; Wang, Wei-Hu; Hu, Chen; Liu, Yue-Ping; Jin, Jing; Liu, Xin-Fan; Yu, Zi-Hao; Ren, Hua; Li, Ning; Lu, Ning-Ning; et al.
Summary: Background: To our knowledge, no randomised study has compared postmastectomy hypofractionated radiotherapy with conventional fractionated radiotherapy in patients with breast cancer. This study aimed to determine whether a 3-week schedule of postmastectomy hypofractionated radiotherapy is as efficacious and safe as a 5-week schedule of conventional fractionated radiotherapy. Methods: This randomised, non-inferiority, open-label, phase 3 study was done in a single academic hospital in China. Patients aged 18–75 years who had undergone mastectomy and had at least four positive axillary lymph nodes or primary tumour stage T3–4 disease were eligible to participate. Patients were randomly assigned (1:1) according to a computer-generated central randomisation schedule, without stratification, to receive chest wall and nodal irradiation at a dose of 50 Gy in 25 fractions over 5 weeks (conventional fractionated radiotherapy) or 43·5 Gy in 15 fractions over 3 weeks (hypofractionated radiotherapy). The modified intention-to-treat population (including all eligible patients who underwent randomisation but excluding those who were considered ineligible or withdrew consent after randomisation) was used in primary and safety analyses. The primary endpoint was 5-year locoregional recurrence, and a 5% margin was used to establish non-inferiority (equivalent to a hazard ratio <1·883). This trial is registered at ClinicalTrials.gov, number NCT00793962 . Findings: Between June 12, 2008, and June 16, 2016, 820 patients were enrolled and randomly assigned to the conventional fractionated radiotherapy group (n=414) or hypofractionated radiotherapy group (n=406). 409 participants in the conventional fractionated radiotherapy group and 401 participants in the hypofractionated radiotherapy group were included in the modified intention-to-treat analyses. At a median follow-up of 58·5 months (IQR 39·2–81·8), 60 (7%) patients had developed locoregional recurrence (31 patients in the hypofractionated radiotherapy group and 29 in the conventional fractionated radiotherapy group); the 5-year cumulative incidence of locoregional recurrence was 8·3% (90% CI 5·8–10·7) in the hypofractionated radiotherapy group and 8·1% (90% CI 5·4–10·6) in the conventional fractionated radiotherapy group (absolute difference 0·2%, 90% CI −3·0 to 2·6; hazard ratio 1·10, 90% CI 0·72 to 1·69; p<0·0001 for non-inferiority). There were no significant differences between the groups in acute and late toxicities, except that fewer patients in the hypofractionated radiotherapy group had grade 3 acute skin toxicity than in the conventional fractionated radiotherapy group (14 [3%] of 401 patients vs 32 [8%] of 409 patients; p<0·0001). Interpretation: Postmastectomy hypofractionated radiotherapy was non-inferior to and had similar toxicities to conventional fractionated radiotherapy in patients with high-risk breast cancer. Hypofractionated radiotherapy could provide more convenient treatment and allow providers to treat more patients. Funding: National Key Projects of Research and Development of China; the Chinese Academy of Medical Science Innovation Fund for Medical Sciences; and Beijing Marathon of Hope, Cancer Foundation of China.